2014
DOI: 10.1002/jlcr.3201
|View full text |Cite
|
Sign up to set email alerts
|

Topical delivery of fluorescence (6‐Cf) labeled and radiolabeled (99m‐Tc) cisplatin and imiquimod by a dual drug delivery system

Abstract: The present investigation deals with the development of topical (top.) formulation for co-delivery of cisplatin and imiquimod to enhance the antitumor efficacy of the drug for skin-cited malignancies even in immune compromised patient. Cisplatin (CDDP) and imiquimod-loaded protransfersome gel (CDDP-Imi-Pts gel) formulation was characterized for entrapment efficiency, pH, and viscosity. Further, fluorescence-labeled (6-carboxyfluorescin) and radiolabeled ((99m) technetium) drug-loaded formulations were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The resultant sediment was resuspended in 0.2 % Triton x-100 (1 mL), and the UV absorbance of the suspension was measured. The total amount of drug comprised the drug present in both sediment and supernatant [14]. The drug content was analysed using UV-1700 spectrophotometer (Shimadzu, India).…”
Section: Assessment Of Entrapment Efficiency Viscosity and Phmentioning
confidence: 99%
“…The resultant sediment was resuspended in 0.2 % Triton x-100 (1 mL), and the UV absorbance of the suspension was measured. The total amount of drug comprised the drug present in both sediment and supernatant [14]. The drug content was analysed using UV-1700 spectrophotometer (Shimadzu, India).…”
Section: Assessment Of Entrapment Efficiency Viscosity and Phmentioning
confidence: 99%
“…13 Numerous studies demonstrated that co-delivery of chemo agents such as OXA and Cis with TLR agonists strengthened the antitumor effect and reduces systemic and immune toxicity compared with chemotherapy alone. 1,11,14,15 The present study attempted to find out whether combination therapy with IMQ, an immune system modulator, plus Cis as ICD inducer agent can trigger potent tumor cell apoptosis with lower cytotoxicity in the A549 lung cancer cell line.…”
Section: Introductionmentioning
confidence: 99%